Investigation of tool wear and chip formation on through hole drilling of mild steel - Nadiah Ahmad Bistaman (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Nowadays, the problem of cutting tool faiures becames important in manufacturing industries. After certain working time at production, tool wear occurs and cutting tool became dulland required a changing. This is because inaccurate selection parameters affect the cutting tool condition.